Pop-Up Books as a Tool for Multisensory Learning: Improving Engagement and Short-term Retention in Early Childhood Education - Estacio, Randel D.; Borja , Ann Kayla A.; Homo, Renzel T.; Sillar, Ramil T. (Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2025)
This study investigates the effectiveness of pop-up books as multisensory learning tools in enhancing engagement and short-term retention among daycare learners in Quezon City, Philippines. Using a quasi-experimental pre-test–post-test design with 60 children aged 3–5 (Experimental = 30; Control = 30), the study measured behavioral, emotional, and cognitive engagement, as well as short-term retention of concepts related to plant care and numeracy. Validated researcher-developed tests (Cronbach’s ? = 0.82) and an engagement scale (? = 0.86) were used, alongside observational checklists. Results indicated significantly higher gains in the experimental group compared with the control group (p < 0.001), demonstrating that tactile and interactive elements in pop-up books promote deeper engagement and improved short-term retention. The findings provide empirical support for integrating low-tech multisensory materials in early childhood education settings.